Analisis determinan pengangguran dan strategi pengurangannya pada Kabupaten/Kota di Provinsi Jambi - Omi Citra, RTM. V; Rachmad.R, Muhammad; Yulmardi, Yulmardi (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2022)
The purpose of this study is to determine the factors that influence unemployment in districts/cities in Jambi province. To formulate strategies for reducing unemployment in districts/cities in Jambi province. This study uses secondary data with panel data regression analysis methods and SWOT analysis. The results of this study that the factors that have a significant effect on unemployment in districts / cities in Jambi Province are Economic Growth, Poverty and Employment Opportunities and a good unemployment reduction strategy is to prevent high labor migration by optimizing the existing workforce in the district/city, building the economy and adequate regional infrastructure, improve the quality of human resources by opening job training and alleviating poverty and unemployment